2019
DOI: 10.1111/sms.13570
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphological determinants of peak power output in elite cyclists

Abstract: Mechanical peak power output (PPO) is a determinant of performance in sprint cycling. The purpose of this study was to examine the relationship between PPO and putative physiological determinants of PPO in elite cyclists, and to compare sprint performance between elite sprint and endurance cyclists. Thirty-five elite cyclists (18 endurance; 17 sprint) performed duplicate sprint cycling laboratory tests to establish PPO and its mechanical components. Quadriceps femoris (Q VOL ) and hamstring muscle volume (HAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 43 publications
6
48
2
Order By: Relevance
“…Peak power output in cycling is proposed to be underpinned by muscle strength, size, and structure 3,25 . The relationship between indices of muscle function and structure is well‐established in heterogenous populations, 4,5 but less‐so in homogenous groups 1 . We hypothesized that changes in muscle function might be concurrent with changes in cycling PPO, but that changes in muscle structure were unlikely given the relatively short duration of training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peak power output in cycling is proposed to be underpinned by muscle strength, size, and structure 3,25 . The relationship between indices of muscle function and structure is well‐established in heterogenous populations, 4,5 but less‐so in homogenous groups 1 . We hypothesized that changes in muscle function might be concurrent with changes in cycling PPO, but that changes in muscle structure were unlikely given the relatively short duration of training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has observed a strong association between peak power output (PPO) and cycling speed, and ergo cycling performance 1‐3 . Implementation of appropriate training to improve PPO is therefore critical to improve sprint track cycling performance 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher increase in the QM stiff in sprint track cyclists may indicate an adaptation to the specific-training loads (Cristi-Sánchez et al, 2019), especially due to mechanical energy transmission during cycling phases (Young et al, 2018). Moreover, Kordi et al (2020) reported a positive relationships between quadriceps muscle volume and peak power output in sprint track cyclists. The alterations in QM stiff after 200 m flying start, observed in our study could be considered by higher power-cadence and torque-cadence in sprinters, than in endurance track cyclists (Kordi et al, 2020).…”
Section: Effect Of 200 M Flying Start and 4000 M Pursuit Race On Qt mentioning
confidence: 90%
“…1 It has also been established that maximum strength heavily influences the ability to generate PPO in elite cyclists. [6][7][8][9] However, little research has been conducted to investigate interventions that could increase maximum strength and hence PPO [7][8][9] , and in particular, using highly-trained or elite level track sprint cyclists.…”
Section: Introductionmentioning
confidence: 99%